Monitoring Perkembangan Anak Usia Balita Berbasis Aplikasi Mobile Android - Febriyanti, Nur Laili; Maulidiansyah, Maulidiansyah; Arifin, Zainal (Universitas Trunojoyo Madura, 2021)
Posyandu is a health activity organized by the community for the community, almost all villages have posyandu activities, including the village of Gunggun Lor. Posyandu in Gunggugan Lor in conveying schedule information, child development, and health information using the MCH book or orally when attending the Posyandu, the consultation process from the midwife is also face-to-face, the process has problems when the MCH book is lost and when the midwife or cadre forgets to convey the information needed, therefore an application is needed as an intermediary to convey the information, namely using a mobile (android) based application, with a modern development method, namely RAD (Rapid Application Development) toddler mother